2011
DOI: 10.1080/10509674.2011.583718
|View full text |Cite
|
Sign up to set email alerts
|

Day Reporting Center and Recidivism: Comparing Offender Groups in a Western Pennsylvania County Study

Abstract: In this study the authors report on an investigation comparing the recidivism and other variables of two similar offender populations in a western Pennsylvania county. The two groups were comparable in offense type, size (N ¼ 63 for each) and other variables such as sex, race and age range. One group represented offenders who received a sentence that included incarceration, whereas the treatment group offenders were sentenced to some form of day reporting and other intermediate punishment measures. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 5 publications
1
10
1
Order By: Relevance
“…Overall, the results of the current analyses directly contrast the findings of prior quasi‐experimental studies in which DRC participants had fewer rearrests in the follow‐up time period than their comparison group counterparts (i.e., Champion et al, ; Martin et al, ). Specifically, medium‐ and high‐risk parolees assigned to a DRC do not fare any better (and occasionally fare worse) than a comparable group of parolees that is placed on traditional parole supervision.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Overall, the results of the current analyses directly contrast the findings of prior quasi‐experimental studies in which DRC participants had fewer rearrests in the follow‐up time period than their comparison group counterparts (i.e., Champion et al, ; Martin et al, ). Specifically, medium‐ and high‐risk parolees assigned to a DRC do not fare any better (and occasionally fare worse) than a comparable group of parolees that is placed on traditional parole supervision.…”
Section: Discussioncontrasting
confidence: 61%
“…Such results are similar to those found in a national survey of DRCs, in which the mean positive termination rate of DRC clients was 50% (Parent, Byrne, Tsarfaty, Valade, and Esselman, ). However, documented completion rates for DRC participation have varied broadly within the available literature, as some researchers have reported program completion rates of less than 40% (Brunet, ; Marciniak, ), whereas others have reported program completion rates of 60% or higher (Champion et al, ; Diggs and Pieper, ; McDevitt and Miliano, ; Roy and Grimes, ). For the current study specifically, the lack of difference in completion rates between DRC participants and Phase I parolees indicates that offenders subject to DRC programming are equally likely to “fail” when compared with parolees on regular parole supervision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that parolees who were referred to DRCs did no better than those who were referred to continued community supervision without DRCs according to several outcomes, and in some instances, they did significantly worse than the non‐DRC group. These findings are notable not only because they represent (to date) results from the most methodologically rigorous assessment of DRCs’ impacts, but also they starkly contrast previous studies that have found DRCs to be associated with favorable outcomes when used as alternatives to revocation and reincarceration (see Champion, Harvey, and Schanz, ; Martin, Lurigio, and Olson, ). The major policy takeaways offered by Boyle et al.…”
supporting
confidence: 43%
“…Boyle et al found that parolees who were referred to DRCs did no better than those who were referred to continued community supervision without DRCs according to several outcomes, and in some instances, they did significantly worse than the non-DRC group. These findings are notable not only because they represent (to date) results from the most methodologically rigorous assessment of DRCs' impacts, but also they starkly contrast previous studies that have found DRCs to be associated with favorable outcomes when used as alternatives to revocation and reincarceration (see Champion, Harvey, and Schanz, 2011;Martin, Lurigio, and Olson, 2003). The major policy takeaways offered by Boyle et al are that DRCs may contribute to increases in returns to incarceration while costing more money to operate than traditional parole supervision, and thus, they do not advise using DRCs as alternatives to incarceration for medium-and high-risk parolees.I respectfully disagree with the policy directions that Boyle et al (2013) propose.…”
mentioning
confidence: 45%